2019
DOI: 10.1038/s41563-019-0462-9
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid–bilirubin nanomedicine for targeted modulation of dysregulated intestinal barrier, microbiome and immune responses in colitis

Abstract: While conventional approaches for inflammatory bowel diseases (IBD) mainly focus on suppressing hyperactive immune responses, it remains unclear how to address disrupted intestinal barriers, dysbiosis of the gut commensal microbiota, and dysregulated mucosal immune responses in IBD. Moreover, immunosuppressive agents can cause off-target systemic side effects and complications. Here, we report the development of hyaluronic acid-bilirubin nanomedicine (HABN) that accumulates in inflamed colonic epithelium and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
359
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(404 citation statements)
references
References 53 publications
(68 reference statements)
9
359
1
3
Order By: Relevance
“…Recently, microbial‐compatible gold nanoparticles and Fe 3 O 4 nanoparticles were used to provide bacteria with capacities of photosynthesis and nanocatalysis, respectively. [ 19–23 ] Whereas, for biomedical purpose, the materials need to be harmless to both bacteria and humans. Prebiotics are a type of polysaccharide that are selectively utilized by probiotics, and more essentially, bring health benefits to the host at the same time.…”
Section: Figurementioning
confidence: 99%
“…Recently, microbial‐compatible gold nanoparticles and Fe 3 O 4 nanoparticles were used to provide bacteria with capacities of photosynthesis and nanocatalysis, respectively. [ 19–23 ] Whereas, for biomedical purpose, the materials need to be harmless to both bacteria and humans. Prebiotics are a type of polysaccharide that are selectively utilized by probiotics, and more essentially, bring health benefits to the host at the same time.…”
Section: Figurementioning
confidence: 99%
“…Hyaluronic acid is also known as a useful treatment option for OA that can modify symptoms and relieve joint pain in OA [49][50][51]. Interestingly, krill oil, astaxanthin, and hyaluronic acid have also been shown to play a role in gut flora modulation, an emerging area of investigation that may also influence the development and progression of osteoarthritis, and symptom management [52][53][54]. Considering the beneficial therapeutic properties of krill oil, astaxanthin, and hyaluronic acid on arthritis, we have developed a novel multi-ingredient dietary supplement formulation, FP-MD, consisting of krill oil, natural astaxanthin, and proprietary lower molecular weight hyaluronic acid, to address the key factors involved in maintaining joint health.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BRNPs protected different cells against cytotoxicity caused by H 2 O 2 and decreased inflammatory responses resulting from activated macrophages. Moreover, other bilirubin-derived nanoparticles can be used as a companion medicine for effective treatment of cancers and colitis (Lee et al, , 2020. As a typical paradigm, Lee et al constructed a hyaluronic acid-bilirubin nanomedicine (HABN) for inhibition of acute colitis (Lee et al, 2020).…”
Section: Bilirubin-derived Nanoparticlesmentioning
confidence: 99%
“…Moreover, other bilirubin-derived nanoparticles can be used as a companion medicine for effective treatment of cancers and colitis (Lee et al, , 2020. As a typical paradigm, Lee et al constructed a hyaluronic acid-bilirubin nanomedicine (HABN) for inhibition of acute colitis (Lee et al, 2020). In vivo experiments demonstrated that HABN could target the inflamed colonic epithelium, restore the dysregulated intestinal barriers, and simultaneously modulate the gut microbiota and immune responses in mice bearing colitis.…”
Section: Bilirubin-derived Nanoparticlesmentioning
confidence: 99%